Investigation of Deep-Level Defects Lateral Distribution in Active Layers of Multicrystalline Silicon Solar Cells. (22nd May 2017) - Litvinov, Vladimir G.; Ermachikhin, Alexander V.; Kusakin, Dmitry S.; Vishnyakov, Nikolay V.; Gudzev, Valery V.; Karabanov, Andrey S.; Karabanov, Sergey M.; Vikhrov, Sergey P.
ABSTRACT: The influence of deep level defects lateral distribution in active layers of multicrystalline Si-based standard solar cells is investigated. Multicrystalline p-type Si wafers with 156×156 mm dimensions and 200 μm thickness were used for SCs preparation. One type of solar cells with conversion efficiency 20.4% was studied using capacitance voltage characteristics method (C-V) and by current deep level transient spectroscopy (I-DLTS). From various places along the diagonal of solar cell's substrate with 20.4% efficiency nine pieces with an area ∼20 mm 2 were extracted and studied. I-DLTS spectra of the five pieces from solar cell were measured. The features of deep levels defects concentration lateral distribution along the SC's surface were studied.